Comparison of isometric strength in rotator cuff and scapulothoracic muscles between elite volleyball athletes versus non-athletes - Piatti, M.; Mosca, A.; Omeljaniuk, R. J.; Turati, M.; Gaddi, D.; Bigoni, M. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Volleyball is an exceptionally popular global sport that involves repetitive, rapid, powerful and wide overhead movements, which can seriously alter normal shoulder kinematics. A recognized hallmark of shoulder muscle balance is the ratio of shoulder external (ER) and internal (IR) rotators. By extension, objective measurement of shoulder muscles` strength could help identify at risk athletes and preempt those injuries by engaging in prescriptive strength training programs. METHODS: This cross-sectional study measured the isometric strengths of 1) shoulder internal and external rotator muscles, as well as the 2) supraspinatus, 3) rhomboid, and 4) middle and inferior trapezius muscles, in addition to calculation of ER:IR ratios, in professional volleyball players as well as in non-athletes. Measurements were made for dominant- and non-dominant upper limbs, in different position of the body (supine and orthostatic) and in different position of upper limb (adducted and abducted position). Our subject population included 11 male professional volleyball players as well as 14 healthy male orthopedic interns from Orthopedics and Trauma school of University of Milano Bicocca. Strengths were assessed by a handheld dynamometer. Each subject`s isometric strength was assessed in triplicate in each limb position through a "make test" procedure; the greatest of each triplicate value was the accepted measure of isometric strength. RESULTS: We observed a gradient in muscle strength in the scapulothoracic complex in both groups; the rhomboid, middle trapezius, and lower trapezius ranked from greatest to least strength, respectively. The data suggest also that intrarotators are stronger in rotation adducted position than in rotation abducted position; however, extrarotators seem to be weaker in rotation adducted position than in rotation abducted position. There is also some indication that force development is enhanced in the supine position compared with the orthostatic position. CONCLUSIONS: Our findings indicate a scapulothoracic strength gradient with a rank order of strength of the rhomboid>middle trapezius>lower trapezius. The data further suggest that volleyball players have stronger intrarotation in rotation adducted position than in the rotation abducted position, while extra rotation shows the opposite trend. Finally, our data suggest that force development is greater in the supine position compared to the orthostatic position.